Development and Validation of a Questionnaire to Measure Perceptions of Freedom of Choice in Digital Games - Sotiris Kirginas; Dimitris Gouscos (Serious Games Society, 2016)
The purposes of this study were (a) to develop a valid and reliable questionnaire using both the structural characteristics of digital games and students perceptions of the concept of freedom of choice in digital games, (b) to validate items to be used in questionnaire to measure perceived freedom of choice, (c) to identify the factors that underlie freedom of choice in digital games and (d) to generate a model to predict preferred freedom of choice in digital games from gender, age, familiarity with digital game and frequency of digital game use. The study consisted of four phases. First, 9 items were developed though a comprehensive literature review and a focus groups method. Second, the items were refined through three layers of review. Third, 290 primary school students rated the results of the reviews. Fourth, exploratory factor analysis (EFA) were employed to analyze the data. The results of the Freedom of Choice (FoC) Questionnaire were statistically significant with a total of 9 items across two factors (exploratory freedom - outcome freedom). Furthermore, a model was constructed, based on a multiple regression, in order to predict preferred freedom of choice in digital games from different demographic characteristics of players. This work can be implemented in serious games; if serious games include the characteristics of free-form play can lead to more engaging and more free-form learning processes, which can better support innovative approaches to learning and, more generally, to the acquisition of 21st century transferable skills.This effort is contextualized within a broader research plan for using digital games (adventure games, in particular) as learning frameworks, with a view to ultimately taking stock of positive player experience drivers, such as freedom of choice, as enablers for better player/learner engagement and more effective learning.